Telephone intervention to promote maternal breastfeeding self-efficacy: randomized clinical trial - Hilana Dayana Dodou; Raylla Araújo Bezerra; Anne Fayma Lopes Chaves; Camila Teixeira Moreira Vasconcelos; Lorena Pinheiro Barbosa; Mônica Oliveira Batista Oriá (SciELO, 2021)
ABSTRACT Objective: To analyze the effects of an educational intervention via telephone on maternal breastfeeding self-efficacy. Method: Randomized controlled clinical trial including 240 puerperae from a secondary care hospital randomized into two groups: control and intervention. The educational intervention took place at seven, 30, 90, and 150 days postpartum and centered on self-efficacy and motivational interviewing principles. Self-efficacy was measured by the Breastfeeding Self-Efficacy Scale - Short Form. The data followed the abnormal distribution, so non-parametric tests were used. Results: The intervention group obtained higher median breastfeeding self-efficacy scores across the three outcome measures when compared to the control group (p < 0,001). Furthermore, the intervention group showed increased self-efficacy scores at all monitoring moments, which shows that the educational intervention was able to raise and maintain women's confidence in breastfeeding their child over time. Conclusion: The use of a telephone-based intervention focused on self-efficacy principles and delivered by trained nurses effectively promoted maternal confidence in breastfeeding. Brazilian Clinical Trial Registry: RBR-7m7vc8.